The Effect of Ideology on the Form and Content of Edward FitzGerald’s Translation of Khayyam's Rubaiyat - Mana Aleahmad (Britain International for Academic Research (BIAR-Publisher), 2021)
The present study attempted to examine Edward FitzGerald, who would translate Omar Khayyam's Rubaiyat (1859), was interested in Persian poetry. Translation deals with power and authority and most of the time the ideology of source text changes in favor of the dominant ideology of target text. Victorian people‘s scornful outlook toward East led to ideological manipulation of source texts by translators such as Fitzgerald. His strange reduction in his translations, especially in Khayyam's Rubaiyat results in the necessity of investigating his translation from ideological point of view. Surprisingly translation of Khayyam’s Rubaiyat has never been studied from ideological perspective and is unknown for many literary scholars. Victorian issues had a strong effect on FitzGerald‘s selection of some Khayyam's Rubaiyat.